Filmen Danske jøder i Hitlers fangenskab - Dethlefsen, Carl Otto (Rambam. Tidsskrift for jødisk kultur og forskning, 2017)
Goodbye Theresienstadt The film Goodbye Theresienstadt was directed by Jonatan Jerichow and the author of this article. This is a short recap of the making of the film and afterthoughts regarding the organisation of the Theresienstadt Concentration Camp. The successful escape of 5000 Danish Jews is a wellknown story, but 472 Danish Jews did not succeed in reaching the shores of neutral Sweden. They were arrested by the Gestapo and deported to Theresienstadt. In the film, we take six of the former inmates back to the camp in order to revisit some of the places of significance to them. Opposite other Jews in the camp, the Danes were allowed to receive parcels with food from home. This was their rescue, as one points out. The Danish Jews were eventually rescued by the so-called White Busses Campaign in the final days of WWII. It was a surprise to the film crew, that the six protagonists firmly stated at the end of their visit: ‘This is our goodbye to Theresienstadt’. After the finishing of the film, the author has been thinking about the attempt by the Nazi bureaucrats to disguise the atrocities of the concentration camps. In Theresienstadt, they made renovations to impress a delegation from the International Red Cross, and they followed up by making a propaganda film. The self-governing system set up by the Germans played a major role in the beautification of the camp, and the chairman of the Elders overseeing this process was Benjamin Murmelstein. The French film director Claude Lanzmann made a film with Murmelstein in which he admitted his role; ‘I was caught between the hammer and the anvil,’ he states in the film. The author elaborates on the huge efforts by the Germans: first, to stage the Potemkin backdrop, and later, to destroy all the evidence by burning archives and throwing urns with victims’ ashes in the river. In Lanzmanns film, Mr. Murmelstein contradicts the famous quote from Hanna Arendt about the banality of Adolf Eichmann. ‘No, he was truly a demon,’ Murmelstein claims. Personal accounts are important as an entrance to understanding the Holocaust, but future generations will not see and hear new eyewitnesses to the atrocities; therefore, testimonials from the last survivors are important to preserve on film. We are proud to have contributed to this with our two films, October 43 and Goodbye Theresienstadt.